2004
DOI: 10.1242/dev.01350
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest cell plasticity and its limits

Abstract: The quail-chick chimera system (see Box 1) has been used over the years to establish a fate map of the NC along the neural axis. These studies have shown that melanocytes arise from the entire length of the NC in higher vertebrates, whereas mesectodermal derivatives originate only from the cephalic NC region. NC-derived cells that contribute to the PNS and ENS arise only from some areas of the neural axis (Fig. 1).Using the quail-chick system, well-defined areas of the NC have been exchanged to assess NCC plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
400
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 499 publications
(420 citation statements)
references
References 142 publications
8
400
1
7
Order By: Relevance
“…During development, Hox genes are expressed in a nested pattern along the body axis (Chisaka and Capecchi, 1991;Creuzet et al, 2002;Wellik and Capecchi, 2003;Le Douarin et al, 2004), where they provide cells with positional information. For example, Hoxa11 and Hoxa13 are expressed in limb mesoderm (Wellik and Capecchi, 2003;Knosp et al, 2004;Rinn et al, 2008), where they regulate patterning and morphogenesis of the fetal appendicular skeleton (Tabin, 1995).…”
Section: An Association Between Embryonic Lineage and Hox Status Mighmentioning
confidence: 99%
See 2 more Smart Citations
“…During development, Hox genes are expressed in a nested pattern along the body axis (Chisaka and Capecchi, 1991;Creuzet et al, 2002;Wellik and Capecchi, 2003;Le Douarin et al, 2004), where they provide cells with positional information. For example, Hoxa11 and Hoxa13 are expressed in limb mesoderm (Wellik and Capecchi, 2003;Knosp et al, 2004;Rinn et al, 2008), where they regulate patterning and morphogenesis of the fetal appendicular skeleton (Tabin, 1995).…”
Section: An Association Between Embryonic Lineage and Hox Status Mighmentioning
confidence: 99%
“…Embryonic cell transplantation experiments have shown that Hox gene expression is a critical determinant of whether grafted cells integrate into their new location (reviewed by Le Douarin et al, 2004). Did a discrepancy in Hox expression underlie the chondrogenic outcome of the adult heterotopic grafts?…”
Section: An Association Between Embryonic Lineage and Hox Status Mighmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential to generate chondrocytes and osteocytes has mainly been attributed to cranial neural crest (NC) cells [1]. In support of this, multipotent progenitors with neural as well as mesenchymal potentials were rarely observed in clonal cell culture assays of trunk NC cells [2,3] and trunk NC was ineffective in forming cartilage after transplantation in vivo [4].…”
Section: Introductionmentioning
confidence: 99%
“…Direct tests of the potency, self-renewal, and molecular characteristics of SKPs and MSCs during late phases of the hair cycle when the stem cell-containing bulge region and the melanocytecontaining hair papilla are physically most discrete should address this issue. Currently, understanding of the in vivo lineage relationships between different types of NCCs is limited, but a detailed model based on extensive characterization of pluripotentiality of cultured NCCs has been proposed by the Le Douarin lab Le Douarin et al, 2004;Dupin et al, 2007). As noted above, several of the intermediates they proposed show at least some capacity for self-renewal (Trentin et al, 2004); as in vivo lineage relationships and progenitor types become clearer, it will be important to establish their self-renewal capacity.…”
Section: Perspectivesmentioning
confidence: 99%